Manjujaji: The Social Function, Local Culture Values, and Universal of Lullabies from West Sumatra, Indonesia - Ninawati Syahrul (Universitas Pendidikan Indonesia, 2025)
Lullabies are a phenomenon that is both local and universal across the globe. Despite their deep local roots, lullabies exist in nearly all cultures worldwide. The Minangkabau society in West Sumatra, Indonesia, have a traditional lullaby practice known as manjujai. However, this tradition is gradually eroding and beginning to fade due to the influence of technology and modernization. Beyond its primary role as a lullaby to lull children to sleep, manjujai also functions as a medium for conveying messages, especially cultural and religious values, intended to be embedded in children’s minds. This study aims to describe, reveal, and analyze the meanings and functions of manjujai as a cultural expression of the Minangkabau community, while connecting its universal values to lullabies in other cultures worldwide. This study employs a qualitative descriptive methodology, with data collected through an analysis of manjujai texts. The findings reveal that manjujai texts serve three social functions: (1) expressing feelings, thoughts, and life attitudes; (2) teaching cultural values through advice, messages, and hopes; (3) presenting linguistic beauty, comfort, tranquility, and well-being for the listening child, The shared essence of lullabies worldwide lies in their expressions of love, gentleness, and care. Many lullabies possess a peaceful, hyponic quality. Fatigue, the darkening night, difficulties in falling asleep, and the act of sleeping itself are universal elements that inspire the melodic and lyrical threads of lullabies worldwide.